FASILITAS BELAJAR SEBAGAI FAKTOR YANG MEMPENGARUHI HASIL BELAJAR IPA KELAS IV SD - Yupinus Hendra (LPPM Universitas Pahlawan Tuanku Tambusai, 2019)
The research conducted aims to analyze the influence of facilities and learning outcomes of fourth grade natural science. The research used is qualitative research where the object being examined is the result of a learning process. Qualitative research is research conducted on natural conditions, which develop as they are, not manipulated by researchers. Qualitative research is generally carried out in the context of evaluation or survey research. The researcher conducted research through observations in several elementary schools in Salatiga with the influence of facilities used during the learning process, The analysis carried out using descriptive analysis. The results of the research obtained on several elementary schools that have been surveyed regarding the facilities and learning outcomes of students namely SD Negeri Salatiga 05 with 33 students, Ledok 06 Elementary School with 14 students, and Kanisius Gendongan Elementary School Salatiga with 39 students. In addition there is an average value of each elementary school as follows: SD Negeri Salatiga 05 with an average value of 71, SD Negeri Ledok 06 with an average value of 60. While SD Kanisius Gendongan Salatiga with an average value of 75 students..